Static and Dynamic Group Migration Algorithms of Virtual Machines to Reduce Energy Consumption of a Server Cluster - Duolikun, Dilawaer; Enokido, Tomoya; Takizawa, Makoto (Transactions on Computational Collective Intelligence XXXIII, 2019)
In prevent global warming, it is critical to reduce electric energy consumed in information systems, especially servers in clusters like cloud computing systems. In this paper, a process migration approach is discussed to reduce the total energy consumption of clusters by using virtual machines. We propose a pair of the static SM(v) and dynamic DM(v) migration algorithms where a group of at most v (≥ $$\ge $$ 0) virtual machines migrate from a host server to a guest server. A group of virtual machines on a host server to migrate to a guest server are selected so that the total energy to be consumed by the host and guest servers can be reduced. In the SM(v) algorithm, the total number of virtual machines is fixed in a cluster. In the DM(v) algorithm, virtual machines are resumed and suspended so that the number of processes on each virtual machine is kept fewer. In the evaluation, we show the total energy consumption of servers can be mostly reduced in the DM(v) algorithm compared with other algorithms.